1129. Targeted Voriconazole Prophylaxis in Heart Transplantation Recipients. (26th November 2018) - Lin, Michael; Echenique, Ignacio; Angarone, Michael; Anderson, Allen; Stosor, Valentina
Abstract: Background: The use of antifungal prophylaxis, targeted or universal, remains controversial and unstudied. The goal of this study is to determine the role of targeted voriconazole prophylaxis (VORI) in prevention of invasive fungal infections (IFI) after heart transplantation (HT). Methods: We conducted a single-center, prospective, observational cohort study of 276 HT recipients from June 2005 to April 2017 to characterize the incidence and outcome of IFI following targeted VORI. Starting in June 2013, HT recipients with thymoglobulin (ATG) treatment received VORI for 3 months. Probable/proven IFI were defined by EORTC/MSG criteria. Descriptive frequencies and univariate analyses were performed. Results: Mean duration of follow-up post-HT was 1, 165 days (0–3, 152 days). 149 (54%) and 70 (25%) received basiliximab and thymoglobulin induction, respectively. Thirty-one (11%) received VORI, following use of ATG in the setting of induction (68%) or rejection (32%). VORI was started at median of 6 days (0–1, 008 days) post-HT for a mean duration of 97 days (5–251 days). Overall, 23 IFIs occurred in 23 recipients (8%) at mean 283 days post-HT (range 2–1, 579 days), including seven Aspergillus (one occurring after VORI completion), seven invasive Candida (five with candidemia), two Rhizopus, one Cunninghamella, two histoplasma, two blastomyces, one Cryptococcus, and one multifocal cutaneous Alternaria. Conclusion: Targeted VORI resulted in reduced incidences of both early and overall IFI after HT although this did not reach statistical significance. Since instituting this strategy, we have observed a single case of aspergillosis following VORI discontinuation. Overall and 1-year mortality were not impacted. The use of antifungal prophylaxis following HT requires continued investigation both to determine efficacy and toxicity in this patient population. Disclosures: All authors: No reported disclosures.